Perivascular Adipose Tissue as an Indication, Contributor to, and Therapeutic Target for Atherosclerosis - Liu, Yan; Sun, Yan; Hu, Chengping; Liu, Jinxing; Gao, Ang; Han, Hongya; Chai, Meng; Zhang, Jianwei; Zhou, Yujie; Zhao, Yingxin (Frontiers in Physiology, 2020)
Perivascular adipose tissue (PVAT) has been identified to have significant endocrine and paracrine functions, such as releasing bioactive adipokines, cytokines, and chemokines, rather than a nonphysiological structural tissue. Considering the contiguity with the vascular wall, PVAT could play a crucial role in the pathogenic microenvironment of atherosclerosis. Growing clinical evidence has shown an association between PVAT and atherosclerosis. Moreover, based on computed tomography, the fat attenuation index of PVAT was verified as an indication of vulnerable atherosclerotic plaques. Under pathological conditions, such as obesity and diabetes, PVAT shows a proatherogenic phenotype by increasing the release of factors that induce endothelial dysfunction and inflammatory cell infiltration, thus contributing to atherosclerosis. Growing animal and human studies have investigated the mechanism of the above process, which has yet to be fully elucidated. Furthermore, traditional treatments for atherosclerosis have been proven to act on PVAT, and we found several studies focused on novel drugs that target PVAT for the prevention of atherosclerosis. Emerging as an indication, contributor to, and therapeutic target for atherosclerosis, PVAT warrants further investigation.